Management of women at increased risk for breast cancer secondary to high‐risk proliferative lesions and family history of the disease. Issue 8 (2nd August 2020) - Cen, Cindy; Chun, Jennifer; Schnabel, Freya
Abstract: Women with breast biopsies showing high‐risk proliferative lesions such as atypical hyperplasia (AH) and lobular carcinoma in situ (LCIS) have an increased risk of developing breast cancer. Other factors including age, family history of breast cancer, and extent of AH may play a role in increasing breast cancer risk. In addition to women with AH, there is a subset of women with a positive family history of breast cancer, without a known germline mutation, which places them also at an increased risk for breast cancer. Clinical management, screening, chemoprevention, and surgical risk‐reduction are discussed in this review to inform the management of these high‐risk women. Advanced imaging technology, pharmacologic research into different targets, and innovations in breast reconstruction are changing the way in which patients are counseled of their individual risk.